Optimization of Production Input Combinations to Achieve The Least Cost Combination - Kholilul Kholik; Aladin Aladin (Sean Institute, 2026)
Operational cost efficiency is a key pillar in maintaining a company's competitiveness amid fluctuations in production factor prices. This study aims to analyze the application of the least cost combination concept in determining the optimal proportion of production inputs (labor and capital) to achieve a specific output target. The analysis method used is based on the Cobb-Douglas production function approach and the use of isocost and isoquant to find the point of tangency that minimizes total costs. The results show that companies often face inefficiencies due to the imbalance of resource allocation in relation to the marginal productivity of each input. By directing the marginal productivity ratio per unit of currency to be equivalent between inputs, companies can reduce budget waste without compromising output quality or quantity. From a managerial perspective, this finding emphasizes the importance of periodically evaluating input prices in the market so that substitutions between production factors can be made accurately to maintain healthy profit margins.